UPAYA UNODC ( UNITED NATIONS OFFICE ON DRUGS AND CRIME ) DALAM MENANGGULANGI PERMASALAHAN NARKOBA DI INDONESIA - Rizki Sari Fadillah; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aims to find out the efforts of the United Nations Office on Drugs and Crime (UNODC) against drug problems in Indonesia. UNODC is one of organizations under the UN Security Council which responsible for fighting various forms of drug trafficking and international crime. UNODC declared drug problems as serious problems for the international community. The effects of drugs can contribute to poor health and death. Not only that, the drug problem also involves the wearer as a drug courier who makes circulation more widespread. These results indicate that the efforts of the UNODC against drug problems in Indonesia by implementing UNODC programs. Some efforts are made the UNODC through alternative development programs to replace the marijuana plants, the global launch of the SMART program as a source of information exchange for Indonesia, implement the program country Indonesia and support pilot rehabilitation projects in Indonesia.Keyword : United Nations Office on Drugs and Crime (UNODC), drugs problem, Alternative Development, Global SMART Programme, Country Programme Indonesia, Pilot Project.